Barrier effects of roads on an endangered forest obligate: influences of traffic, road edges, and gaps. (July 2016) - Chen, Hsiang Ling; Koprowski, John L.
Abstract: Habitat fragmentation and destruction caused by development of infrastructure such as roads threaten biodiversity. Roads act as barriers by impeding animal movements and restricting space use. Understanding factors that influence barrier effects is important to discern the impacts of habitat fragmentation and to develop appropriate mitigations. We combined telemetry and demographic data in 2008 to 2012 with remote sensing imagery to investigate barrier effects of forest roads and assess effects of traffic, road edges, and canopy gaps on space use of an endangered, endemic forest obligate, the Mt. Graham red squirrel ( Tamiasciurus hudsonicus grahamensis ). We mapped low to high traffic roads, road edges, canopy gaps, and random lines in forests to serve as references. We determined if red squirrels included these linear features in their total and core home ranges, and used this metric as an indicator of crossing and preference for habitat adjacent to the linear features. Forest roads acted as barriers regardless of traffic volume and had long-term impacts on animal space use. Animals did not avoid entering roadside areas, and probability of crossing linear features in the forest was not affected by distance to roads. In contrast, greater canopy cover increased probability of crossing, and gaps in canopy impeded animal movements. Higher likelihood of road crossing was associated with more variable tree height and mating activity. We demonstrated that narrow forest roads with low traffic volume were barriers for forest dependent species, and suggest that gap avoidance inhibits road crossings. Highlights: We used long-term demographic and telemetry data. We assessed effects of roads, traffic, and distance to roads simultaneously on space use and movements of small mammals. We showed effects of environment, animal activities, and social interactions on probability of road crossing. Narrow forest roads with low traffic volume were barriers for forest dependent species, likely due to gap avoidance. Higher likelihood of road crossing was associated with more variable tree height and mating activity.